THE EFFECT OF HEALTHCARE WORKER ON THE PATIENT’S SAFETY MEDIATED BY BURNOUT AT KARTINI MOTHER'S AND CHILD HOSPITAL IN PADALARANG - Dalton Ngangi; PM. Budi Haryono; Wani Devita Gunardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This research has the intention to look for the mediated effect of burnout on healthcare workers against patient's safety. Respondents of this study were the healthcare workers of the Hospital of Mother and Child Kartini Padalarang. The testing of the hypothesis was conducted by using quantative research method with the total sample of 100 healthcare workers. Datas were collected through electronic questionnaires that were given digitally to the respondents. The analysis technique that was used was the Partial Least Square - Structural Equation Modelling (PLS-SEM) from the SmartPLS program. Based on the analyzed data, it was found that there was a significant effect of workload and healthcare workers against the patient's safety and that healthcare workers had an important role in mediating it. Based on this research's result, it was found that the workload has a significant negative effect on the patient's safety, burnout on healthcare providers has no effect on patient's safety and the healthcare workers have a positive effect on the patient's safety. The Hospital of Mother and Child Kartini Padalarang needs to consider improving th wellbeing and professionality of the healthcare workers in order to keep the job satisfaction well maintained. The Hospital of Mother and Child Kartini Padalarang also needs to hold a good working relationship with the healthcare workers and the patients, so that the patient's satisfaction and safety are well maintained.